Fishing gears and methods in the Chalan Beel, Bangladesh - Nahid Sultana; M Nazrul Islam (Journal of Fisheries, 2016)
Present study on fishing gears and methods in the Chalan Beel was conducted during the period of July 2011 to June 2014. The Chalan Beel is the large network of fluvial waters body that harbors rich ichthyofaunal diversity. Most of the fishing methods of the Chalan Beel are primitive, based on indigenous traditional knowledge and well suited to turbulent nature of the streams. In this study thirty fishing methods and gears have been documented and classified into five categories- fishing nets, traps, wounding gears, hooks and lines, and others. Many of these were harmful to fishes as well as aquatic biodiversity. Effective measurements are required to make proper use of the Chalan Beel.